Synthesis of 1-Aminocyclopropyl-Pentanoic and -Heptanoic Acid Derivatives - Gensini, Martina; Quartara, Laura; Altamura, Maria (Letters in Organic Chemistry, 2008)
Herein we report the synthesis of new (1-amino-cyclopropyl)-pentanoic and -heptanoic acid derivatives by titanium- mediated reductive cyclopropanation of the correspondent amides.
Keywords: amines